Polyanionic precursor, sodium-ion battery positive electrode material, preparation method of sodium-ion battery positive electrode material, sodium-ion battery and power-related equipment
By using the chemical formula NaqMm+nM’wPxOy·zH2O of the polyanionic precursor, the sodium ion battery positive electrode material was prepared through two-step reaction, and the problems of low purity and low compaction density in the prior art were solved, and a positive electrode material with high purity, high compaction density and high conductivity were achieved.
Patent Information
- Application Number
- CN202410845544.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-06-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing methods for preparing the positive electrode material of sodium ion battery have problems such as uneven mixing, difficult to control the ratio of metal to P, low purity and low energy density, and the types and applications are limited.
The chemical general formula of polyanionic precursor is adopted to prepare the precursor through a two-step reaction, controlling the element distribution and proportion, and improving the purity and compaction density of the material.
The high purity (≥95%), high compaction density and ideal morphology of the cathode material are achieved, reducing the amount of sodium source added, reducing production costs, and improving conductivity and stability.
Smart Images

Figure CN119637831A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion batteries, and in particular to a polyanion precursor, a sodium ion battery positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] Polyanion cathode materials are a very important type of existing sodium ion battery cathode materials and have received widespread attention in the field of energy storage.
[0003] At present, the solid phase method is the main preparation method of polyanion cathode materials. However, due to the inherent defect of uneven mixing, the ratio of metal to P in the obtained material is difficult to control and the purity is low. In addition, the existing technology mainly focuses on metal elements mainly based on Fe, and the types and applications of polyanion cathode materials are greatly limited.
[0004] The one-step solid-phase synthesis method has the problem of large sintering gas production, which leads to low energy density, compaction density, and tap density of the positive electrode material, affecting its commercial application. Summary of the invention
[0005] The purpose of the present application is to provide a polyanion precursor, a sodium ion battery positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] The present application provides a polyanionic precursor, the general chemical formula of which is Na q M m+n M' w P x O y · zH2O;
[0008] Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; m represents M 2+ The content of M 3+ content, 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.70≤(m+n+w) / x≤0.82, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, x, and y are selected according to the valence state of M' so that the chemical formula maintains charge balance.
[0009] Optionally, the polyanionic precursor satisfies one or more of the following conditions:
[0010] (1) M is Fe and Mn;
[0011] (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y;
[0012] (3) 0.40≤q / (m+n+w)≤0.65;
[0013] (4) 0.26≤q / x≤0.60;
[0014] (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26;
[0015] (6) 0≤w / (m+n)≤0.05;
[0016] (7) 0.71≤(m+n+w) / x≤0.77;
[0017] (8) The valence state of M' is +α, q+2m+3n+αw+5x=2y;
[0018] (9) The valence state of M' is +α, 1≤α≤5; or, 2≤α≤4;
[0019] (10) 0≤z / (m+n+w)≤6; or, 0≤z / (m+n+w)≤3;
[0020] (11) The polyanionic precursor contains phosphate and / or pyrophosphate;
[0021] (12) The polyanionic precursor contains pyrophosphate, and the P content in the pyrophosphate accounts for more than 10 wt% of the total P content in the polyanionic precursor;
[0022] (13) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%;
[0023] (14) In the polyanionic precursor, the content of P is 15wt% to 25wt%;
[0024] (15) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%;
[0025] (16) In the polyanionic precursor, the content of S is less than 0.5 wt %;
[0026] (17) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %;
[0027] (18) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%;
[0028] (19) In the polyanionic precursor, the content of the impurity element is less than 3.0 wt %; or, the content of the impurity element is less than 1.5 wt %;
[0029] (20) In the polyanionic precursor, n(S):n(M+M')≤0.1, or n(S):n(M+M')≤0.06;
[0030] (21) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, or n(S+N):n(M+M')≤0.06;
[0031] (22) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, or n(S+N+C):n(P)≤0.06;
[0032] (23) The polyanionic precursor is in an amorphous state;
[0033] (24) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ;
[0034] (25) The BET of the polyanionic precursor is 5 to 25 m 2 / g;
[0035] (26) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm;
[0036] (27) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm;
[0037] (28) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm;
[0038] (29) The primary particles of the polyanionic precursor are spherical or quasi-spherical;
[0039] (30) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°;
[0040] (31) The polyanionic precursor is poorly soluble in water;
[0041] (32) The polyanionic precursor conforms to the chemical formula Na q M m+n M' w P x Oy ·zH2O.
[0042] As the same inventive concept, the present application also provides a polyanionic precursor, containing a chemical formula of Na q M m+n M' w (PO4) e (P2O7) f · Substances containing H2O;
[0043] Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; m represents M 2+ The content of M 3+ content, 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.68≤(m+n+w) / (e+2f)≤0.80, 0≤e / (e+2f)≤0.90, 0.1≤2f / (e+2f)≤1, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, e, and f are selected according to the valence state of M' so that the chemical formula maintains charge balance.
[0044] The above general formula Na q M m+n M' w P x O y P in zH2O x O y Including phosphate and pyrophosphate, that is, the general formula can also be written as Na q M m+n M' w (PO4) e (P2O7) f ·zH2O, that is, x=e+2f, y=4e+7f.
[0045] Optionally, the polyanionic precursor satisfies one or more of the following conditions:
[0046] (1) M is Fe and Mn;
[0047] (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y;
[0048] (3) 0.40≤q / (m+n+w)≤0.65;
[0049] (4) 0.26≤q / (e+2f)≤0.60;
[0050] (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26;
[0051] (6) 0≤w / (m+n)≤0.05;
[0052] (7)0.71≤(m+n+w) / (e+2f)≤0.77;
[0053] (8) The valence state of M' is +α, q+2m+3n+αw+5(e+2f)=2(4e+7f);
[0054] (9) The valence state of M' is +α, 1≤α≤5; or, 2≤α≤4;
[0055] (10) 0≤z / (m+n+w)≤6; or, 0≤z / (m+n+w)≤3;
[0056] (11) The polyanionic precursor contains phosphate and / or pyrophosphate;
[0057] (12) The polyanionic precursor contains pyrophosphate, and the P content in the pyrophosphate accounts for more than 10 wt% of the total P content in the polyanionic precursor;
[0058] (13) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%;
[0059] (14) In the polyanionic precursor, the content of P is 15wt% to 25wt%;
[0060] (15) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%;
[0061] (16) In the polyanionic precursor, the content of S is less than 0.5 wt %;
[0062] (17) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %;
[0063] (18) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%;
[0064] (19) In the polyanionic precursor, the content of the impurity element is less than 3.0 wt %; or, the content of the impurity element is less than 1.5 wt %;
[0065] (20) In the polyanionic precursor, n(S):n(M+M')≤0.1, or n(S):n(M+M')≤0.06;
[0066] (21) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, or n(S+N):n(M+M')≤0.06;
[0067] (22) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, or n(S+N+C):n(P)≤0.06;
[0068] (23) The polyanionic precursor is in an amorphous state;
[0069] (24) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ;
[0070] (25) The BET of the polyanionic precursor is 5 to 25 m 2 / g;
[0071] (26) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm;
[0072] (27) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm;
[0073] (28) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm;
[0074] (29) The primary particles of the polyanionic precursor are spherical or quasi-spherical;
[0075] (30) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°;
[0076] (31) The polyanionic precursor is poorly soluble in water;
[0077] (32) The polyanionic precursor conforms to the chemical formula Na q M m+n M' w (PO4) e (P2O7) f ·zH2O.
[0078] The present application also provides a method for preparing a polyanionic precursor, comprising the following steps:
[0079] Step A: Add M 2+ A metal salt and a first phosphorus source containing pyrophosphate are mixed to obtain a mixed solution, and a first reaction is performed to obtain a mixed solution containing a pyrophosphate salt of a divalent metal M;
[0080] Step B: adding an oxidant and a second phosphorus source to a mixed solution of pyrophosphate containing a divalent metal M to carry out a second reaction, separating the solid and the liquid after the second reaction, and drying the separated solid to obtain the polyanionic precursor; wherein the first phosphorus source and / or the second phosphorus source contain sodium ions.
[0081] Optionally, the preparation method of the polyanionic precursor satisfies one or more of the following conditions:
[0082] (1) The M-containing 2+ The metal salt includes one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt; 2+ The metal salt is one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt;
[0083] (2) The M-containing 2+ The metal salt includes one or more of sulfate, nitrate and chloride;
[0084] (3) The M-containing 2+ The metal salt also contains a soluble salt of metal M';
[0085] (4) the first phosphorus source and / or the second phosphorus source comprises pyrophosphate and / or sodium pyrophosphate;
[0086] (5) The temperature of the first reaction is 50 to 80° C., and the time of the first reaction is 1 to 10 hours;
[0087] (6) The oxidant is hydrogen peroxide;
[0088] (7) the molar amount of phosphorus in the pyrophosphate ion accounts for not less than 70% of the total molar amount of phosphorus in the first phosphorus source and the second phosphorus source;
[0089] (8) introducing an oxygen-containing gas during the second reaction;
[0090] (9) The temperature of the second reaction is 55 to 85° C., and the time of the second reaction is 1 to 6 hours;
[0091] (10) aging after the second reaction, the aging time is 5 to 20 hours;
[0092] (11) The drying temperature is 80 to 120° C.;
[0093] (12) The molar ratio of phosphorus in the first phosphorus source to that in the second phosphorus source is 2.5 to 3.6:1;
[0094] (13) The raw materials of the polyanionic precursor do not contain a carbon source.
[0095] As the same inventive concept, the present application also provides a polyanion type sodium ion battery positive electrode material, the raw materials of the polyanion type sodium ion battery positive electrode material include a polyanion type precursor, a sodium source and a carbon source.
[0096] As the same inventive concept, the polyanionic precursor is the polyanionic precursor defined by the above chemical formula, or the polyanionic precursor obtained by the above method for preparing the polyanionic precursor.
[0097] As the same inventive concept, the present application also provides a polyanion type sodium ion battery positive electrode material, wherein the component of the polyanion type sodium ion battery positive electrode material is a composite of sodium phosphate pyrophosphate metal salt and carbon;
[0098] In the sodium phosphate pyrophosphate metal salt, the metals other than sodium include M and optional M'; wherein M is one or more of Fe, Ni, Co, and Mn; and M' is selected from one or more of transition metal elements other than M, Mg, Ca, Sr, and Al.
[0099] Optionally, the polyanion sodium ion battery positive electrode material meets one or more of the following conditions:
[0100] (1) The compaction density of the polyanion sodium ion battery positive electrode material is 1.8 to 2.4 g / cm 3 ;
[0101] (2) The specific surface area of the polyanion sodium ion battery positive electrode material is 5 to 25 m 2 / g;
[0102] (3) The average particle size of the primary particles of the polyanion sodium ion battery positive electrode material is 100 to 400 nm;
[0103] (4) The average particle size D50 of the secondary particles of the polyanion sodium ion battery positive electrode material is 1 to 5 μm;
[0104] (5) The crystal structure of the sodium phosphophosphate metal salt belongs to the Pn21a space group;
[0105] (6) The composition of sodium phosphophosphate is Na4M j M' k (PO4)2P2O7; where 0≤k / j≤0.1, 2.8≤j+k≤3.2;
[0106] (7) The S content of the polyanion sodium ion battery positive electrode material is ≤0.08wt%; or, the S content is ≤0.05wt%;
[0107] (8) The N content of the polyanion sodium ion battery positive electrode material is ≤0.08wt%; or, the N content is ≤0.05wt%.
[0108] As the same inventive concept, the present application also provides a method for preparing the polyanion sodium ion battery positive electrode material, comprising:
[0109] The raw materials including the polyanion precursor, the carbon source and the sodium source are mixed, crushed, dried and then sintered to obtain the polyanion sodium ion battery positive electrode material;
[0110] Optionally, the method for preparing the polyanion sodium ion battery positive electrode material satisfies one or more of the following conditions:
[0111] (1) The carbon source is one or more of sucrose, glucose, crystal sugar, cellulose, phenolic resin, polyethylene glycol, polyvinyl pyrrolidone, starch, polyvinyl alcohol, ionic cellulose gum carbon source, and inorganic carbon source;
[0112] (2) The sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate, and sodium oxalate;
[0113] (3) The pulverization is grinding or sand milling;
[0114] (4) The sintering temperature is 500-600° C., and the sintering time is 6-30 hours.
[0115] As the same inventive concept, the present application also provides a sodium ion battery, comprising the polyanion sodium ion battery positive electrode material.
[0116] As the same inventive concept, the present application also provides an electrical equipment, including the sodium ion battery.
[0117] Compared with the prior art, the beneficial effects of this application include:
[0118] The polyanion precursor provided by the present application has uniform distribution of elements and low content of impurities; the polyanion precursor contains a certain amount of Na, which can reduce the amount of sodium source added during the preparation of the positive electrode material, which is beneficial to cost saving. The elements in the precursor are uniformly distributed, and it is very easy to obtain a high-purity positive electrode material using it as a raw material, with a purity of ≥95%.
[0119] The polyanionic precursor provided in the present application is obtained by a two-step reaction. The morphology of the precursor is easy to control, and a relatively ideal morphology is easy to obtain, and the tap density is relatively high. The ratio of metal M+M' to P is highly close to the ratio required for the positive electrode material (such as 3:4), and there is no need to additionally supplement metal M and M' to P. The process is simple, and no harmful gases containing N and S are generated during sintering, which is environmentally friendly.
[0120] The sodium ion battery positive electrode material provided in the present application uses the above-mentioned polyanion precursor as a raw material. The obtained positive electrode material can fully react with the electrolyte and can reduce the sodium ion transmission distance, thereby effectively improving the conductivity and stability of the positive electrode material.
[0121] The positive electrode material prepared by the polyanion precursor in the present application has few pores and the characteristics of high compaction, and the positive electrode material has the characteristics of high purity, high capacity and stable structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0122] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0123] Figure 1 This is a SEM image of the precursor prepared in Example 2;
[0124] Figure 2a This is the XRD pattern of the precursor prepared in Example 2;
[0125] Figure 2b XRD patterns of the precursor prepared in Example 2 after being calcined at 500° C. and 600° C. for 12 h respectively;
[0126] Figure 3 This is the XRD pattern of the precursor prepared in Example 21;
[0127] Figure 4 This is the XRD pattern of the positive electrode material obtained in Comparative Example 2;
[0128] Figure 5 This is the XRD pattern of the positive electrode material obtained in Example 3;
[0129] Figure 6 This is a SEM image of the positive electrode material prepared in Example 3;
[0130] Figure 7 This is the infrared test spectrum of the precursor obtained in Example 5;
[0131] Figure 8 This is the first week charge and discharge curve of the positive electrode material electrode obtained in Example 5. DETAILED DESCRIPTION
[0132] As used herein:
[0133] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0134] The conjunction "consisting of" excludes any unspecified element, step, or component. If used in a claim, this phrase will make the claim closed, so that it does not include materials other than those described, except for the usual impurities associated therewith. In this application, open-ended expressions (such as: comprising, containing, including) include the meaning of closed expressions.
[0135] In this application, open expressions (such as: include, contain, include) all include the meaning of closed expressions.
[0136] In the present application, "a plurality of types" means two or more, and "a plurality" means two or more.
[0137] When quantity, concentration, or other value or parameter is expressed as a range, an optional range, or a range limited by a series of upper and lower optional values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or optional value with any range lower limit or optional value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0138] In this application, wt% means mass percentage, mol% means molar percentage, and vol% means volume percentage. When the meaning of % is not indicated, it refers to mass percentage. When calculating the mass percentage of a certain element / substance in a precursor, the total mass of the precursor should include the mass of crystal water, but should exclude the mass of free water.
[0139] In the present application, n(A) represents the number of moles of element / substance A, and n(A+B) represents the sum of the number of moles of elements / substances A and B. n(A):n(B) represents the molar ratio of elements / substances A and B.
[0140] Unless otherwise specified, the "polyanionic precursor" in this application is often referred to as "precursor".
[0141] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0142] In order to solve the problems of large gas production, low compaction and easy generation of impurities in the preparation of polyanionic positive electrode materials in the prior art, the present application adopts the idea of first preparing a polyanionic precursor and then preparing the positive electrode material, which makes it easy to obtain a positive electrode material with high purity and high compaction, while at the same time, the emission of harmful gases is extremely small, achieving a relatively ideal comprehensive effect.
[0143] The present application provides a polyanion precursor, including a general chemical formula of Na q M m+n M' w P x O y · zH2O; Optionally, the polyanionic precursor conforms to the above chemical formula;
[0144] Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, Al, and; m represents M 2+ The content of M 3+ The content of 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.68≤(m+n+w) / x≤0.80, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, x, and y are selected according to the valence state of M' so that the chemical formula maintains charge balance.
[0145] In certain optional embodiments, the target product of the above-mentioned polyanionic precursor provided in the present application is a phosphate pyrophosphate type positive electrode material, such as the common sodium iron phosphate pyrophosphate, also known as: sodium iron pyrophosphate, and its chemical formula is: Na4Fe3(PO4)2(P2O7); similarly, when iron is replaced by nickel, cobalt or manganese, it can also be sodium nickel phosphate pyrophosphate, sodium cobalt phosphate pyrophosphate, and sodium manganese phosphate pyrophosphate. This type of positive electrode material usually also contains carbon materials to improve its conductivity. The four elements of iron, nickel, cobalt, and manganese are adjacent in position in the periodic table, have similar chemical properties, and have valence states of +2 and +3 at the same time, and can all be used in phosphate pyrophosphate type positive electrode materials. Therefore, the polyanionic precursor materials of the present application use iron, nickel, cobalt, and manganese as the main metal elements, and the corresponding target positive electrode materials can be obtained.
[0146] In the above general formula, compared with the main metal element M, the content of M' is very low, and M' can be understood as a doping element. In some embodiments, the introduction of doping elements is a commonly used technical means in the field of positive electrode materials, and doping will improve the performance of certain aspects of the positive electrode material. Since the content of the doping element M' is very low, it will not have a great impact on the structure of the target positive electrode material, and the target positive electrode material can still be formed through the precursor. Therefore, the sodium phosphate pyrophosphate metal salt used in this application represents a compound containing phosphate, pyrophosphate, sodium and other non-sodium metals, wherein the non-sodium metal is the main metal element M and the optional doping element M'.
[0147] To make the description as concise as possible, the polyanionic precursor of the present application is represented by the above chemical formula. It is understandable that in some embodiments, hydrogen may exist in the phosphate and pyrophosphate groups, so in some embodiments, in addition to the crystal water, the above formula still contains hydrogen.
[0148] In certain embodiments, P x O y Mainly represents phosphate and pyrophosphate. In some embodiments, phosphate and pyrophosphate include hydrogen-containing situations, that is, phosphate or pyrophosphate may contain one or more hydrogens, including monohydrogen phosphate, dihydrogen phosphate, monohydrogen pyrophosphate, dihydrogen pyrophosphate, trihydrogen pyrophosphate, etc.
[0149] In the above general formula, the relative ratio of each element in the general formula is used to define the formula. In some embodiments, the molar number of a certain element can be defined as an integer for ease of expression, such as the molar number of the M element m+n=1. The molar number of the sum of multiple elements can also be defined as an integer, such as the sum of the molar numbers of the M and M' elements m+n+w=1.
[0150] This application uses infrared to qualitatively test the content of phosphate and pyrophosphate and finds that 750cm -1 The position on the left and right represents a characteristic peak (POP) of pyrophosphate, which has a weak signal and is difficult to characterize quantitatively. The present application refers to an article by Qiu Xingchu et al., published in the journal Material Protection in December 2000 (Issue 12, Volume 33), "Photometric Determination of Phosphate and Pyrophosphate in Copper Pyrophosphate Plating Solution", to quantitatively test pyrophosphate. However, since the precursor is insoluble in water, it is necessary to use acid to dissolve it before testing, and pyrophosphate can be partially converted into phosphate under acidic conditions. Therefore, the pyrophosphate obtained by the present application according to the method can represent the lower limit of the pyrophosphate content in the polyanionic precursor.
[0151] In the above general formula, the content of crystalline water can be measured by thermogravimetric analysis. In certain embodiments, the temperature at which the crystalline water of the precursor is completely dehydrated is about 400°C.
[0152] In the above general formula, except for the crystal water, the oxygen content is calculated by valence balancing.
[0153] The elements in the above general formula include Na, M, M', P, H, O, and the remaining elements can be regarded as miscellaneous elements. Most of the miscellaneous elements are harmful elements. For example, due to the limitations of the preparation process, there are some impurities such as S and N (usually due to the use of raw materials containing sulfates, nitrates, and ammonium salts). These impurities will cause harmful gases to be generated when the precursor is sintered into positive electrode materials. Therefore, the lower the content of these elements, the better. Non-harmful elements, such as carbon, can also exist among the miscellaneous elements.
[0154] In the above general formula, q represents the Na content. After the precursor obtained in the experiment was washed with water many times, the Na content was still relatively high. It can be seen that this part of Na is insoluble. The presence of this part of Na can make it possible to add less sodium source when the precursor is sintered into a positive electrode material.
[0155] M 2+ Represents a divalent element M, M 3+ represents a trivalent element M;
[0156] M 2+ The proportion is small. Optionally, m / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35 or any value between 0 and 0.35; when m / (m+n)=0, that is, m=0, it means that M is not contained 2+ ;
[0157] M' accounts for a small proportion, and optionally, w / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any value between 0 and 0.1; when w / (m+n)=0, that is, w=0, it means that the chemical formula does not contain the element M';
[0158] The total molar amount of M and M' and the total molar amount of phosphorus need to be maintained at about 3:4 to obtain the target positive electrode material product. Without considering doping, in some embodiments, the target positive electrode material can be Na4M3(PO4)2P2O7. Generally, the closer the molar ratio of the precursor material metal M to P is to 3:4, the higher the purity of the positive electrode material Na4M3(PO4)2P2O7 will be.
[0159] Optionally, q / (m+n+w) can be 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70 or any value between 0.32 and 0.70;
[0160] Optionally, (m+n+w) / x can be 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80 or any value between 0.68-0.80; z / (m+n+w) can be 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or any value between 0-10; z represents the amount of crystal water, and z=0 means that there is no crystal water;
[0161] In the prior art, sodium source, carbon source, iron source, phosphorus source are usually blended in liquid or solid phase and then sintered, and the mixture after blending and before sintering is regarded as a precursor. The polyanionic precursor of the present application mainly provides a phosphorus source and a non-sodium metal source for the target positive electrode material, that is, a sodium source and a carbon source still need to be added during the sintering of the positive electrode material. Since the precursor of the present application already contains some Na, the demand for a sodium source during the sintering of the positive electrode material will be reduced.
[0162] In an optional embodiment, the polyanionic precursor satisfies one or more of the following conditions:
[0163] (1) M is Fe and Mn;
[0164] (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y;
[0165] (3) 0.40≤q / (m+n+w)≤0.65;
[0166] Optionally, q / (m+n+w) can be 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65 or any value between 0.40 and 0.65;
[0167] (4) 0.26≤q / x≤0.60;
[0168] Optionally, q / x can be 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60 or any value between 0.26 and 0.60;
[0169] (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26;
[0170] Optionally, m / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33 or any value between 0 and 0.33;
[0171] (6) 0≤w / (m+n)≤0.05;
[0172] Optionally, w / (m+n) may be 0, 0.01, 0.02, 0.03, 0.04, 0.05 or any value between 0 and 0.05;
[0173] (7) 0.71≤(m+n+w) / x≤0.77;
[0174] Optionally, (m+n+w) / x may be 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77 or any value between 0.73 and 0.77;
[0175] (8) According to charge balance, when the valence state of M' is +α, ignoring the influence of other elements, q+2m+3n+αw+5x=2y;
[0176] The valence state of the doping element M' is +α, and among the common doping metal elements, 1≤α≤5;
[0177] Optionally, α may be 1, 2, 3, 4 or 5; Optionally, 2≤α≤4;
[0178] (9) 0≤z / (m+n+w)≤6; optionally, 0≤z / (m+n+w)≤3;
[0179] Optionally, z / (m+n+w) can be 0, 1, 2, 3, 4, 5, 6 or any value between 0 and 6;
[0180] (10) The polyanionic precursor contains phosphate and / or pyrophosphate; optionally, the P content in the pyrophosphate accounts for more than 10% of the total P content in the polyanionic precursor;
[0181] It should be noted that if acid is added during the reaction, at least part of the pyrophosphate will be converted into phosphate, so the precursor will contain both phosphate and pyrophosphate.
[0182] (11) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%;
[0183] Optionally, in the polyanionic precursor, the content of Na may be 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value between 4wt% and 10wt%;
[0184] (12) In the polyanionic precursor, the content of P is 15wt% to 25wt%;
[0185] Optionally, in the polyanionic precursor, the content of P may be 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt% or any value between 15wt% and 25wt%;
[0186] (13) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%;
[0187] Optionally, in the polyanionic precursor, the total content of M and M' can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt% or any value between 20wt% and 32wt%;
[0188] (14) In the polyanionic precursor, the content of S is less than 0.5 wt %;
[0189] Optionally, in the polyanionic precursor, the content of S may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.49wt% or any value less than 0.5wt%;
[0190] (15) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %;
[0191] The S and N impurities in the polyanionic precursor are often due to the presence of sulfate and nitrate in the raw materials. The polyanionic precursor in the present application is difficult to dissolve in water, while sulfate and nitrate are soluble in water. Therefore, the S and N impurities can be easily removed by solid-liquid separation to achieve a lower content.
[0192] Optionally, in the polyanionic precursor, the total content of S and N may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt% or any value less than 0.8wt%;
[0193] (16) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%;
[0194] Optionally, in the polyanionic precursor, the total content of S, N and C may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or any value less than 1.0wt%;
[0195] (17) In the polyanionic precursor, the content of the impurity elements is less than 3.0 wt %; optionally, the content of the impurity elements is less than 1.5 wt %;
[0196] Optionally, in the polyanionic precursor, the total content of heteroelements may be 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt% or any value less than 3.0wt%;
[0197] (18) In the polyanionic precursor, n(S):n(M+M')≤0.1, and optionally n(S):n(M+M')≤0.06;
[0198] Optionally, in the polyanionic precursor, n(S):n(M+M') may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0199] (19) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, and optionally n(S+N):n(M+M')≤0.06;
[0200] Optionally, in the polyanionic precursor, n(S+N):n(M+M') may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0201] (20) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, and optionally n(S+N+C):n(P)≤0.06;
[0202] Optionally, in the polyanionic precursor, n(S+N+C):n(P) may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0203] (21) The polyanionic precursor is in an amorphous state, and XRD testing can identify that the polyanionic precursor has poor crystallinity;
[0204] In an optional embodiment, the polyanionic precursor satisfies one or more of the following conditions:
[0205] (22) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ;
[0206] Optionally, the tap density TD of the polyanionic precursor may be 0.9 g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 Or 0.9~1.4g / cm 3 Any value between
[0207] (23) The BET of the polyanionic precursor is 5 to 25 m 2 / g;
[0208] Optionally, the BET of the polyanionic precursor may be 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g or 5~25m 2 Any value between / g;
[0209] (24) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm;
[0210] Optionally, the average particle size of the primary particles of the polyanionic precursor may be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 50 and 200 nm;
[0211] (25) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm;
[0212] Optionally, the average particle size D50 of the secondary particles of the polyanionic precursor may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value between 1 and 10 μm;
[0213] (26) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm;
[0214] Optionally, the polyanionic precursor D10 can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or any value less than or equal to 1μm, and D90 can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any value less than or equal to 50μm.
[0215] (27) The primary particles of the polyanionic precursor are spherical or quasi-spherical;
[0216] (28) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°;
[0217] Optionally, in the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak may be 26°, 27°, 28°, 29°, 30°, 31°, 32° or any position between 26° and 32°;
[0218] (29) The polyanionic precursor is poorly soluble in water.
[0219] As the same inventive concept, the present application also provides a polyanionic precursor, containing a chemical formula of Na q M m+n M' w (PO4) e (P2O7) f · Substances containing H2O;
[0220] Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; m represents M 2+ The content of M 3+ content, 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.68≤(m+n+w) / (e+2f)≤0.80, 0≤e / (e+2f)≤0.90, 0.1≤2f / (e+2f)≤1, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, e, and f are selected according to the valence state of M' so that the chemical formula maintains charge balance.
[0221] Optionally, m / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35 or any value between 0 and 0.35; when m / (m+n)=0, that is, m=0, it means that M is not contained 2+; w / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any value between 0 and 0.1; when w / (m+n)=0, that is, w=0, it means that the chemical formula does not contain element M'; q / (m+n+w) can be 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0 .58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70 or any value between 0.32 and 0.70; (m+n+w) / (e+2f) can be 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80 or any value between 0.68 and 0.80; e / (e+2f) can be 0, 0.01, 0.02, 0.03, 0.4, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12 2. 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.3 7, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.6 2, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90 or any value between 0 and 0.90, when e / (e+2f)=0, that is, e=0, it means that there is no phosphate group; 2f / (e+2f) can be 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0 .47、0.48、0.49、0.50、0.51、0.52、0.53、0.54、0.55、0.56、0.57、0.58、0.59、0.60、0.61、0.62、0.63、0.64、0.65、0.66、0.67、0.68、0.69、0.70、0.71、0.72、 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1 or any value between 0.1-1; z / (m+n+w) can be 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or any value between 0-10; z represents the amount of crystal water, and z=0 means that there is no crystal water. .
[0222] Optionally, the polyanionic precursor satisfies one or more of the following conditions:
[0223] (1) M is Fe and Mn;
[0224] (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y;
[0225] (3) 0.40≤q / (m+n+w)≤0.65;
[0226] Optionally, q / (m+n+w) can be 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65 or any value between 0.40 and 0.65;
[0227] (4) 0.26≤q / (e+2f)≤0.60;
[0228] Optionally, q / (e+2f) can be 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60 or any value between 0.26 and 0.60;
[0229] (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26;
[0230] Optionally, m / (m+n) can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33 or any value between 0 and 0.33;
[0231] (6) 0≤w / (m+n)≤0.05;
[0232] Optionally, w / (m+n) may be 0, 0.01, 0.02, 0.03, 0.04, 0.05 or any value between 0 and 0.05;
[0233] (7)0.71≤(m+n+w) / (e+2f)≤0.77;
[0234] Optionally, (m+n+w) / (e+2f) may be 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77 or any value between 0.73 and 0.77;
[0235] (8) The valence state of M' is +α, q+2m+3n+αw+5(e+2f)=2(4e+7f);
[0236] (9) The valence state of M' is +α, 1≤α≤5; or, 2≤α≤4;
[0237] Optionally, α can be 1, 2, 3, 4, or 5;
[0238] (10) 0≤z / (m+n+w)≤6; or, 0≤z / (m+n+w)≤3;
[0239] Optionally, z / (m+n+w) can be 0, 1, 2, 3, 4, 5, 6 or any value between 0 and 6;
[0240] (11) The polyanionic precursor contains phosphate and / or pyrophosphate;
[0241] (12) The polyanionic precursor contains pyrophosphate, and the P content in the pyrophosphate accounts for more than 10 wt% of the total P content in the polyanionic precursor;
[0242] (13) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%;
[0243] Optionally, in the polyanionic precursor, the content of Na may be 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value between 4wt% and 10wt%;
[0244] (14) In the polyanionic precursor, the content of P is 15wt% to 25wt%;
[0245] Optionally, in the polyanionic precursor, the content of P may be 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt% or any value between 15wt% and 25wt%;
[0246] (15) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%;
[0247] Optionally, in the polyanionic precursor, the total content of M and M' can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt% or any value between 20wt% and 32wt%;
[0248] (16) In the polyanionic precursor, the content of S is less than 0.5 wt %;
[0249] Optionally, in the polyanionic precursor, the content of S may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.49wt% or any value less than 0.5wt%;
[0250] (17) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %;
[0251] Optionally, in the polyanionic precursor, the total content of S and N may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt% or any value less than 0.8wt%;
[0252] (18) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%;
[0253] Optionally, in the polyanionic precursor, the total content of S, N and C may be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or any value less than 1.0wt%;
[0254] (19) In the polyanionic precursor, the content of the impurity element is less than 3.0 wt %; or, the content of the impurity element is less than 1.5 wt %;
[0255] Optionally, in the polyanionic precursor, the total content of heteroelements may be 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt% or any value less than 3.0wt%;
[0256] (20) In the polyanionic precursor, n(S):n(M+M')≤0.1, or n(S):n(M+M')≤0.06;
[0257] Optionally, in the polyanionic precursor, n(S):n(M+M') may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0258] (21) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, or n(S+N):n(M+M')≤0.06;
[0259] Optionally, in the polyanionic precursor, n(S+N):n(M+M') may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0260] (22) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, or n(S+N+C):n(P)≤0.06;
[0261] Optionally, in the polyanionic precursor, n(S+N+C):n(P) may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value less than or equal to 0.1;
[0262] (23) The polyanionic precursor is in an amorphous state;
[0263] (24) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ;
[0264] Optionally, the tap density TD of the polyanionic precursor may be 0.9 g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 Or 0.9~1.4g / cm 3 Any value between
[0265] (25) The BET of the polyanionic precursor is 5 to 25 m 2 / g;
[0266] Optionally, the BET of the polyanionic precursor may be 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g or 5~25m 2 Any value between / g;
[0267] (26) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm;
[0268] Optionally, the average particle size of the primary particles of the polyanionic precursor may be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 50 and 200 nm;
[0269] (27) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm;
[0270] Optionally, the average particle size D50 of the secondary particles of the polyanionic precursor may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value between 1 and 10 μm;
[0271] (28) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm;
[0272] Optionally, the polyanionic precursor D10 can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or any value less than or equal to 1μm, and D90 can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any value less than or equal to 50μm.
[0273] (29) The primary particles of the polyanionic precursor are spherical or quasi-spherical;
[0274] (30) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°;
[0275] Optionally, in the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak may be 26°, 27°, 28°, 29°, 30°, 31°, 32° or any position between 26° and 32°;
[0276] (31) The polyanionic precursor is poorly soluble in water;
[0277] (32) The polyanionic precursor conforms to the chemical formula Na q M m+n M' w (PO4) e (P2O7) f ·zH2O.
[0278] The present application also provides a method for preparing a polyanionic precursor, comprising the following steps:
[0279] Step A: Add M 2+ A metal salt and a first phosphorus source containing pyrophosphate are mixed to obtain a mixed solution, and a first reaction is performed to obtain a mixed solution containing a pyrophosphate salt of a divalent metal M;
[0280] Step B: adding an oxidant and a second phosphorus source to a mixed solution of pyrophosphate containing a divalent metal M to carry out a second reaction, separating the solid and the liquid after the second reaction, and drying the separated solid to obtain the polyanionic precursor; wherein the first phosphorus source and / or the second phosphorus source contain sodium ions.
[0281] In an optional embodiment, the method for preparing the polyanionic precursor satisfies one or more of the following conditions:
[0282] (1) The M-containing 2+ The metal salt includes one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt; 2+ The metal salt is one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt;
[0283] (2) The M-containing 2+ The metal salt includes one or more of sulfate, nitrate and chloride;
[0284] (3) The M-containing 2+ The metal salt also contains a soluble salt of metal M';
[0285] (4) the first phosphorus source and / or the second phosphorus source comprises sodium pyrophosphate;
[0286] (5) The temperature of the first reaction is 50 to 80° C., and the time of the first reaction is 1 to 10 hours;
[0287] Optionally, the temperature of the first reaction may be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value between 50 and 80°C, and the time of the first reaction may be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value between 1 and 10h;
[0288] (6) The oxidant is hydrogen peroxide;
[0289] (7) the molar amount of phosphorus in the pyrophosphate ion accounts for not less than 70% of the total molar amount of phosphorus in the first phosphorus source and the second phosphorus source;
[0290] Optionally, the ratio of the molar amount of phosphorus in the pyrophosphate to the total molar amount of phosphorus in the first phosphorus source and the second phosphorus source may be 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol%, 95 mol% or any value not less than 70%;
[0291] (8) introducing an oxygen-containing gas during the second reaction;
[0292] (9) The temperature of the second reaction is 55 to 85° C., and the time of the second reaction is 1 to 6 hours; optionally, the temperature of the second reaction can be 55, 60, 65° C., 70° C., 75° C., 80° C., 85° C., or any value between 55 and 85° C., and the time of the second reaction can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any value between 1 and 6 hours;
[0293] (10) aging after the second reaction, the aging time is 5 to 20 hours;
[0294] Optionally, the aging time can be 5 h, 10 h, 15 h, 20 h, or any value between 5 and 20 h;
[0295] (11) The drying temperature is 80 to 120° C.;
[0296] Optionally, the drying temperature may be 80°C, 90°C, 100°C, 110°C, 120°C or any value between 80 and 120°C.
[0297] (12) The molar ratio of phosphorus in the first phosphorus source to that in the second phosphorus source is 2.5 to 3.6:1.
[0298] Optionally, the molar ratio of phosphorus in the first phosphorus source and the second phosphorus source can be 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1 or any value between 2.5 and 3.6:1.
[0299] (13) The raw material does not contain a carbon source.
[0300] The target product of the preparation method is the above-mentioned polyanionic precursor, which does not contain carbon, so no carbon source needs to be added in the selection of raw materials. Therefore, even if carbon-containing substances (such as carbonates) are added to the raw materials, the carbon-containing substances cannot be regarded as carbon sources.
[0301] As the same inventive concept, the present application also provides a polyanion type sodium ion battery positive electrode material, the raw materials of the polyanion type sodium ion battery positive electrode material include a polyanion type precursor, a sodium source and a carbon source.
[0302] In certain embodiments, the polyanionic precursor is the polyanionic precursor defined by the above chemical formula, or the polyanionic precursor obtained by the above method for preparing the polyanionic precursor.
[0303] In some embodiments, the polyanion sodium ion battery positive electrode material obtained has a composition of Na4M j M' kA complex of (PO4)2P2O7 and carbon;
[0304] Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; 0≤k / j≤0.1, 2.8≤j+k≤3.2;
[0305] It is understandable that the general formula is Na4M j M' k The molar ratio of Na, phosphate and pyrophosphate in (PO4)2P2O7 may fluctuate to a certain extent, such as the molar ratio of Na to P may deviate from 1:1. Therefore, the general formula can be more accurately understood as sodium metal phosphate pyrophosphate.
[0306] Optionally, k / j can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value between 0 and 0.1, and j+k can be 2.8, 2.9, 3.0, 3.1, 3.2 or any value between 2.8 and 3.2.
[0307] The polyanion sodium ion battery positive electrode material meets one or more of the following conditions:
[0308] (1) The compaction density of the polyanion sodium ion battery positive electrode material is 1.8 to 2.4 g / cm 3 ;
[0309] Optionally, the compaction density of the polyanion sodium ion battery positive electrode material can be 1.8 g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 or 1.9~2.4g / cm 3 Any value between
[0310] (2) The specific surface area of the polyanion sodium ion battery positive electrode material is 5 to 25 m 2 / g;
[0311] Optionally, the specific surface area of the polyanion sodium ion battery positive electrode material can be 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g or 5~25m 2 Any value between / g;
[0312] (3) The average particle size of the primary particles of the polyanion sodium ion battery positive electrode material is 100 to 400 nm;
[0313] Optionally, the average particle size of the primary particles of the polyanion sodium ion battery positive electrode material may be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm or any value between 100 and 400 nm;
[0314] (4) The average particle size D50 of the secondary particles of the polyanion sodium ion battery positive electrode material is 1 to 5 μm.
[0315] Optionally, the average particle size D50 of the secondary particles of the sodium ion battery positive electrode material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between 1 and 5 μm.
[0316] As the same inventive concept, the present application also provides a polyanion type sodium ion battery positive electrode material, wherein the component of the polyanion type sodium ion battery positive electrode material is a composite of sodium phosphate pyrophosphate metal salt and carbon; in the sodium phosphate pyrophosphate metal salt, the metal other than sodium includes M and M' which is not necessarily present; wherein M is one or more of Fe, Ni, Co, and Mn; M' is selected from one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; the polyanion type sodium ion battery positive electrode material satisfies one or more of the following conditions:
[0317] (1) The S content of the polyanion sodium ion battery positive electrode material is ≤ 0.08 wt%; optionally, the S content is ≤ 0.07 wt%, 0.06 wt%, 0.05 wt%, 0.04 wt%, 0.03 wt%, 0.02 wt%, 0.01 wt% or 0.005 wt%; in particular, when the raw material of the polyanion sodium ion battery positive electrode material includes a S-containing compound, the S content of the positive electrode material can still be maintained within the above range;
[0318] (2) The N content of the polyanionic sodium ion battery positive electrode material is ≤0.08wt%; optionally, the N content is ≤0.07wt%, 0.06wt%, 0.05wt%, 0.04wt%, 0.03wt%, 0.02wt%, 0.01wt% or 0.005wt%; in particular, when the raw material of the polyanionic sodium ion battery positive electrode material includes a N-containing compound, the N content of the positive electrode material can still be maintained within the above range.
[0319] In certain embodiments, the present application also provides a method for preparing the polyanion sodium ion battery positive electrode material, comprising:
[0320] The raw materials including the polyanion precursor, the carbon source and the sodium source are mixed, crushed, dried and then sintered to obtain the polyanion sodium ion battery positive electrode material;
[0321] Typically, sintering is performed under a protective atmosphere, such as a nitrogen atmosphere.
[0322] In an optional embodiment, the preparation method of the polyanion sodium ion battery positive electrode material meets one or more of the following conditions:
[0323] (1) The carbon source is one or more of sucrose, glucose, crystal sugar, cellulose, phenolic resin, polyethylene glycol, polyvinyl pyrrolidone, starch, polyvinyl alcohol, ionic cellulose gum carbon source, and inorganic carbon source;
[0324] (2) The sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate, and sodium oxalate;
[0325] (3) The pulverization is grinding or sand milling;
[0326] (4) The sintering temperature is 500-600° C., and the sintering time is 6-30 hours.
[0327] Optionally, the sintering temperature can be 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃ or any value between 500 and 600℃, and the sintering time can be 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h or any value between 6 and 30h.
[0328] The present application also provides a sodium ion battery, comprising the polyanion sodium ion battery positive electrode material.
[0329] The present application also provides an electrical device, including the sodium ion battery.
[0330] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0331] The amount of carbon source (such as glucose) is calculated based on the total mass of the precursor and the sodium source (such as sodium carbonate). For example, 10% glucose in Example 1 means that the added mass of glucose is 10% of the total mass of the precursor and sodium carbonate.
[0332] Example 1
[0333] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0334] 3 mol of ferrous sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, and the reaction was carried out for 4 hours. Then 450 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the temperature was maintained at 70°C for 2 hours, and aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.738 (molar ratio).
[0335] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0336] 1 mol of the precursor was mixed with 2 mol of sodium carbonate, 10% of glucose [wherein 10% of glucose means that the amount of glucose added accounts for 10% of the total mass of the raw materials (precursor + sodium carbonate), the same below], and 5 L of acetone, and then ball-milled for 12 hours, vacuum-dried for 10 hours, and then sintered in an atmosphere furnace at 540°C for 12 hours in a nitrogen atmosphere to obtain the target product, sodium ferric phosphate pyrophosphate.
[0337] Example 2
[0338] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0339] 3 mol of ferrous sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 75°C, and the reaction was carried out for 6 hours. Then 300 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the temperature was maintained at 75°C for 3 hours, and aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.763 (molar ratio).
[0340] Figure 1 This is the SEM image of the precursor prepared in Example 2. Figure 1 It can be seen that the primary particles of the precursor are tightly packed together, thus having a higher tap density.
[0341] Figure 2a XRD pattern of the precursor prepared in Example 2, the sample is amorphous; Figure 2bThe following are XRD patterns of the precursor prepared in Example 2 after being calcined at 500°C (upper curve) and 600°C (lower curve) for 12 hours. After calcination at 600°C, a sodium-containing phase appeared, proving that the precursor contains sodium. Figure 2b It can be seen that even after calcination at 500°C, the product still has poor crystallinity and is amorphous.
[0342] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0343] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 12% glucose and 5 L of ethanol, ball-milled for 12 h, vacuum-dried for 10 h, and then sintered in an atmosphere furnace at 550° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0344] Example 3
[0345] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0346] 3 mol of ferrous sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, and the reaction was carried out for 8 hours. Then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, and the temperature was maintained at 80°C for 3 hours. Air was simultaneously introduced for oxidation and aged for 12 hours. The precipitate was filtered and washed three times. The collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.740 (molar ratio).
[0347] This embodiment provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0348] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, and then ball-milled for 12 h and sand-milled for 1 h. After vacuum drying for 10 h, the mixture was placed in an atmosphere furnace and sintered at 520° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0349] Figure 5 This is the XRD diagram of the positive electrode material obtained in Example 3. XRD shows pure phase Na4Fe3(PO4)2(P2O7).
[0350] Figure 6 This is the SEM image of the Na4Fe3(PO4)2(P2O7) positive electrode material prepared in Example 3. The product inherits the primary particle morphology of the precursor, is spherical and tightly packed together, and is nanometer-sized.
[0351] Example 4
[0352] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0353] 3 mol of ferrous sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 8 hours, and then 600 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the temperature was maintained at 80°C for 3 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.746 (molar ratio).
[0354] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0355] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, and then ball-milled for 12 h and sand-milled for 1 h. After vacuum drying for 10 h, the mixture was placed in an atmosphere furnace and sintered at 550° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0356] Example 5
[0357] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0358] 3 mol of ferrous sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 10 hours, and then 500 ml of hydrogen peroxide and 1 mol of disodium hydrogen phosphate were added to the reactor, the temperature was maintained at 80°C for 6 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.756 (molar ratio).
[0359] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0360] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0361] Figure 7 This is the infrared test spectrum of the precursor obtained in Example 5. It can be observed that 1050cm -1 PO2 nearby 2- The characteristic peak of 750cm -1 There is a characteristic peak of POP nearby, 545cm -1 There is a PO nearby 2- The characteristic peaks of the product prove that the product contains pyrophosphate.
[0362] Example 6
[0363] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0364] 3 mol of ferrous nitrate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 420 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.731 (molar ratio).
[0365] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0366] 1 mol of the precursor was mixed evenly with 2.0 mol of sodium carbonate, 15% glucose and 5 L of water, ball milled for 12 h and sand milled for 1 h, vacuum dried for 10 h and then sintered in an atmosphere furnace at 520° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0367] Example 7
[0368] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0369] 3 mol of ferrous nitrate and 1.56 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 60°C, the reaction was carried out for 6 hours, and then 440 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 65°C for 3 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.722 (molar ratio).
[0370] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0371] 1 mol of the precursor was mixed evenly with 2.0 mol of sodium carbonate, 15% glucose and 5 L of water, ball milled for 12 h and sand milled for 1 h, vacuum dried for 10 h and then sintered in an atmosphere furnace at 520° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0372] Example 8
[0373] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0374] 3 mol of ferrous sulfate and 1.50 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 440 ml of hydrogen peroxide and 0.68 mol of sodium pyrophosphate were added to the reactor, and the reaction was carried out at a temperature of 75°C for 3 hours. Air was simultaneously introduced for oxidation and aged for 12 hours. The precipitate was filtered and washed three times. The collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.694 (molar ratio).
[0375] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0376] 1 mol of the precursor was mixed evenly with 2.0 mol of sodium carbonate, 15% glucose and 5 L of water, ball milled for 12 h and sand milled for 1 h, vacuum dried for 10 h and then sintered in an atmosphere furnace at 520° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0377] Example 9
[0378] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0379] 3 mol of ferrous sulfate and 1.50 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 440 ml of hydrogen peroxide and 0.40 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an iron-to-phosphorus ratio of 0.790 (molar ratio).
[0380] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0381] 1 mol of the precursor was mixed evenly with 2.0 mol of sodium carbonate, 15% glucose and 5 L of water, ball milled for 12 h and sand milled for 1 h, vacuum dried for 10 h and then sintered in an atmosphere furnace at 520° C. for 12 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0382] Example 10
[0383] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0384] 2.7 mol of ferrous sulfate, 0.3 mol of magnesium sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at a temperature of 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor (molar ratio) with (M+M') / P of 0.730. Wherein M = Fe, M' = Mg, Fe / Mg = 91 / 9 (molar ratio).
[0385] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0386] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, magnesium-doped sodium iron pyrophosphate.
[0387] Embodiment 11
[0388] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0389] 2.85 mol of ferrous sulfate, 0.15 mol of copper sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at a temperature of 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with (M+M') / P of 0.733 (molar ratio). Wherein M=Fe, M'=Cu, Fe / Cu=96 / 4 (molar ratio).
[0390] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0391] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, copper-doped sodium iron phosphate pyrophosphate.
[0392] Example 12
[0393] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0394] 2.94 mol of ferrous sulfate, 0.06 mol of titanyl sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at a temperature of 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with (M+M') / P of 0.735 (molar ratio). Wherein M=Fe, M'=Ti, Fe / Ti=98 / 2 (molar ratio).
[0395] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0396] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, titanium-doped sodium iron pyrophosphate.
[0397] Embodiment 13
[0398] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0399] 2.7 mol of ferrous sulfate, 0.3 mol of nickel sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium dihydrogen phosphate were added to the reactor, the reaction was carried out at a temperature of 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.740 (molar ratio). Fe accounted for 90 mol% of the total M, and Ni accounted for 10 mol%.
[0400] Embodiment 14
[0401] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0402] 2.7 mol of ferrous sulfate, 0.3 mol of nickel sulfate and 1.52 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.747 (molar ratio). Fe accounted for 91 mol% of the total M, and Ni accounted for 9 mol%.
[0403] Embodiment 15
[0404] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0405] 2.7 mol of ferrous sulfate, 0.3 mol of cobalt sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 8 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium dihydrogen phosphate were added to the reactor for 4 hours, and air was introduced for oxidation at the same time, and aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.739 (molar ratio). Fe accounted for 92 mol% of the total M, and Co accounted for 8 mol%.
[0406] Example 16
[0407] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0408] 2.7 mol of ferrous sulfate, 0.3 mol of cobalt sulfate and 1.52 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.745 (molar ratio). Fe accounted for 92 mol% of the total M, and Co accounted for 8 mol%.
[0409] Embodiment 17
[0410] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0411] 2.85 mol of ferrous sulfate, 0.15 mol of manganese sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.736. Fe accounted for 95 mol% of the total M, and Mn accounted for 5 mol%.
[0412] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0413] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0414] Embodiment 18
[0415] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0416] 2.91 mol of ferrous sulfate, 0.09 mol of manganese sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 420 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.734. Fe accounted for 97 mol% of the total M, and Mn accounted for 3 mol%.
[0417] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0418] 1 mol of the precursor was mixed evenly with 2 mol of sodium carbonate, 15% of glucose and 5 L of water, sand-milled for 3 h, spray-dried and sintered in an atmosphere furnace at 500° C. for 13 h in a nitrogen atmosphere to obtain the target product, sodium iron phosphate pyrophosphate.
[0419] Embodiment 19
[0420] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0421] 2.7 mol of ferrous sulfate, 0.3 mol of manganese sulfate and 1.50 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at a temperature of 75°C for 3 hours, and air was introduced for oxidation at the same time, and the aging was carried out for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.743. Fe accounted for 90 mol% of the total M, and Mn accounted for 10 mol%.
[0422] Embodiment 20
[0423] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0424] 2.7 mol of ferrous sulfate, 0.3 mol of manganese sulfate and 1.50 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.741. Fe accounted for 90 mol% of the total M, and Mn accounted for 10 mol%.
[0425] Embodiment 21
[0426] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0427] 1.5 mol of ferrous sulfate, 1.5 mol of manganese sulfate and 1.50 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.751. Fe accounted for 49 mol% of the total M, and Mn accounted for 51 mol%.
[0428] Embodiment 22
[0429] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0430] 1.5 mol of ferrous sulfate, 1.5 mol of manganese sulfate and 1.52 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 80°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with an M / P ratio of 0.746. Fe accounted for 50 mol% of the total M, and Mn accounted for 50 mol%.
[0431] Embodiment 23
[0432] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0433] 3 mol of manganese sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 60°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium dihydrogen phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The product was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Mn / P ratio of 0.746 (molar ratio). Figure 3 This is the XRD pattern of the precursor prepared in Example 21. The sample is amorphous.
[0434] Embodiment 24
[0435] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0436] 3 mol of manganese sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Mn / P ratio of 0.752 (molar ratio).
[0437] Embodiment 25
[0438] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0439] 3 mol of manganese sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 60°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Mn / P ratio of 0.741 (molar ratio).
[0440] Embodiment 26
[0441] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0442] 3 mol of manganese sulfate and 1.5 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Mn / P ratio of 0.748 (molar ratio).
[0443] Embodiment 27
[0444] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0445] 2.9 mol manganese sulfate, 0.1 mol copper sulfate and 1.53 mol sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 60°C, the reaction was carried out for 6 hours, 400 ml hydrogen peroxide and 1 mol sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced simultaneously for oxidation, the reaction was aged for 12 hours, the precipitate was filtered and washed three times, the collected filter cake was dried at 100°C for 16 hours, and a precursor with (M+M') / P of 0.745 (molar ratio) was prepared. Wherein M=Mn, M'=Cu, Mn / Cu=97 / 3 (molar ratio).
[0446] Embodiment 28
[0447] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0448] 2.8 mol manganese sulfate, 0.2 mol aluminum sulfate and 1.53 mol sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml hydrogen peroxide and 0.5 mol sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, air was introduced simultaneously for oxidation, and the reaction was aged for 12 hours. The precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with (M+M') / P of 0.741 (molar ratio). Among them, M=Mn, M'=Al, and Mn / Al=94 / 6 (molar ratio).
[0449] Embodiment 29
[0450] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0451] 3.0 mol of nickel sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Ni / P ratio of 0.768 (molar ratio).
[0452] Embodiment 30
[0453] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0454] 3.0 mol of nickel sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Ni / P ratio of 0.778 (molar ratio).
[0455] Embodiment 31
[0456] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0457] 3.0 mol of cobalt sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 0.5 mol of sodium pyrophosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Co / P ratio of 0.787 (molar ratio).
[0458] Embodiment 32
[0459] This embodiment provides a polyanionic precursor, and the preparation method thereof is as follows:
[0460] 3.0 mol of cobalt sulfate and 1.53 mol of sodium pyrophosphate were mixed evenly in a 5L reactor, the reaction temperature was controlled at 70°C, the reaction was carried out for 6 hours, and then 400 ml of hydrogen peroxide and 1 mol of sodium phosphate were added to the reactor, the reaction was carried out at 75°C for 3 hours, and air was introduced simultaneously for oxidation. The mixture was aged for 12 hours, the precipitate was filtered and washed three times, and the collected filter cake was dried at 100°C for 16 hours to prepare a precursor with a Co / P ratio of 0.783 (molar ratio).
[0461] Comparative Example 1
[0462] This comparative example provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0463] Mix 3 mol of ferrous sulfate, 4 mol of ammonium dihydrogen phosphate, 2 mol of sodium carbonate, 10% glucose [wherein, 10% glucose means that the amount of glucose added accounts for 10% of the total mass of the raw materials] and 5 L of acetone, then ball mill for 12 hours, vacuum dry for 10 hours, and then sinter in an atmosphere furnace at 540°C for 12 hours in a nitrogen atmosphere to obtain the target product Na4Fe3(PO4)2(P2O7).
[0464] Comparative Example 2
[0465] This comparative example provides a sodium ion battery positive electrode material, and the preparation method thereof is as follows:
[0466] Mix 3 mol of ferric phosphate, 1 mol of ammonium dihydrogen phosphate, 2 mol of sodium carbonate, 10% glucose [10% glucose means that the amount of glucose added accounts for 10% of the total mass of the raw materials] and 5 L of water evenly, sand grind for 2 hours, spray dry and granulate, and then sinter in an atmosphere furnace at 520°C in a nitrogen atmosphere for 14 hours to obtain the target product Na4Fe3(PO4)2(P2O7).
[0467] Figure 4 This is the XRD diagram of the positive electrode material obtained in Comparative Example 2. XRD shows obvious impurity phase NaFePO4.
[0468] The elemental analysis results of the precursors prepared in Examples 1-12 are compared, and the results are shown in Tables 1, 2, 3, and 4 below. The main elements of the precursors are Fe / P, and a small amount of Na is contained. Some embodiments contain a small amount of doping elements. The elemental analysis results of the precursors prepared in Examples 13-22 are compared, and the results are shown in Table 5 below. The main elements of the precursors are Fe, (Ni / Co / Mn), and P, and a small amount of Na is contained. The elemental analysis results of the precursors prepared in Examples 23-28 are compared, and the results are shown in Table 6 below. The main elements of the precursors are Mn and P, and a small amount of Na is contained. Some embodiments contain a small amount of doping elements. The elemental analysis results of the precursors prepared in Examples 29-30 are compared, and the results are shown in Table 7 below. The main elements of the precursors are Ni and P, and a small amount of Na is contained. The elemental analysis results of the precursors prepared in Examples 31-32 are compared, and the results are shown in Table 8 below. The main elements of the precursors are Co and P, and a small amount of Na is contained. The particle size analysis results of the precursors and positive electrode materials prepared in Examples 1-12 and Comparative Examples 1-2 were compared, and the results are shown in Table 10. The S, N, and C element analysis results of the positive electrode materials prepared in Examples 1-12 and Comparative Examples 1-2 were compared, and the results are shown in Table 9.
[0469] The iron content was determined by referring to the potassium dichromate titration method (GB 4102.2-83), the P content was determined by referring to the quinoline phosphomolybdic acid gravimetric method (YS T 1028.3-2015), and other metal elements and S were tested by ICP.
[0470] Table 1 Elemental analysis results of precursors
[0471]
[0472] Table 2 Elemental analysis results of precursors
[0473] Example Fe, wt% <![CDATA[Fe 2+ ,wt%]]> P, wt% Na, wt% N, wt% Iron-phosphorus ratio Fe precipitation rate, % P precipitation rate, % Example 6 26.65 2.67 20.22 6.92 0.16 0.731 98.84 99.91 Example 7 26.09 1.04 20.03 7.35 0.25 0.722 96.26 97.08
[0474] Table 3 Elemental analysis results of precursors
[0475] Example Fe, wt% <![CDATA[Fe 2+ ,wt%]]> P, wt% Na, wt% S, wt% Iron-phosphorus ratio Fe precipitation rate, % P precipitation rate, % Example 8 25.17 1.53 20.11 6.59 0.15 0.694 98.24 97.36 Example 9 28.61 1.77 20.08 6.92 0.18 0.790 98.55 98.47
[0476] Table 4 Elemental analysis results of precursors
[0477]
[0478] Table 5 Elemental analysis results of precursors
[0479]
[0480]
[0481] Table 6 Elemental analysis results of precursors
[0482]
[0483] Table 7 Elemental analysis results of precursors
[0484]
[0485] Table 8 Elemental analysis results of precursors
[0486]
[0487] Table 9 Element analysis results of positive electrode materials
[0488]
[0489]
[0490] Table 10 Particle size test results
[0491]
[0492] According to the total Fe, Fe 2+ The test results of P and Na show that the theoretical chemical formula of Example 1 obtained by balancing the general formula is Na 0.54 Fe (0.21+0.79) P 1.36 O 5.05 1.53H2O. It is understandable that due to test errors and the possible presence of impurity elements or elements that cannot be measured, the theoretical molecular formula may deviate from the actual one to a certain extent. The theoretical molecular formula is obtained based on the test results of various elements and valence balance calculations, assuming that the molar number of Fe is 1. The theoretical chemical formulas of other embodiments are not described in detail.
[0493] The pyrophosphate content of Examples 1-3 was tested using the method of the document "Photometric Determination of Phosphate and Pyrophosphate in Copper Pyrophosphate Plating Solution", and the test results are shown in Table 11. Test steps: Accurately weigh 1g of the precursor sample, use an appropriate amount of concentrated hydrochloric acid to fully dissolve it at room temperature, and use a spectrophotometer to measure the phosphate content in the sample. Take another 1g of the precursor sample, use an appropriate amount of concentrated hydrochloric acid to fully dissolve it in a heated state, use a spectrophotometer to measure the total phosphorus content, and then subtract the phosphate content from the total phosphorus content to obtain the pyrophosphate test result. Since the use of concentrated hydrochloric acid to dissolve at room temperature will cause the pyrophosphate to be partially converted into phosphate, the pyrophosphate value tested by this method will be low.
[0494] The direct test result of the above method is the pyrophosphate content (wt%), that is, the percentage of the mass of P in the pyrophosphate to the total mass of the precursor, see the second column of data in Table 11. The third column of data in Table 11 is the total content of P in the polyanionic precursor obtained by other methods (derived from Table 1); the fourth column of data in Table 11 is obtained by dividing the second column of data by the third column of data, representing the ratio of P in the pyrophosphate to the total P in the precursor.
[0495] Table 11 Pyrophosphate test results of precursors
[0496]
[0497] The comprehensive indicators of the positive electrode materials prepared in some embodiments and comparative examples are compared, and the results are shown in Table 12 below:
[0498] Table 12 Performance indicators
[0499]
[0500]
[0501] As shown in Table 12 above, the method provided by the present application can be used to prepare a positive electrode material with high compaction density and high gram capacity. Since the precursor primary particles prepared by the liquid phase precipitation method have good crystallinity and high tap density, it is beneficial to fully contact and react with the sodium source as a matrix during sintering, so the obtained positive electrode material also has a large compaction density and tap density. In addition, the primary particle size of the positive electrode material after sintering is 100-400nm, which is beneficial to the full infiltration reaction of the positive electrode material and the electrolyte, and can reduce the sodium ion transmission distance, thereby effectively improving the conductivity and stability of sodium iron pyrophosphate, thereby obtaining a positive electrode material with a large gram capacity. Figure 5This is the XRD comparison diagram of the positive electrode material product of Example 3. It can be seen that the product has a high diffraction peak intensity and a narrow half-peak width, which is a high-purity positive electrode material. The main phase components are: Na4Fe3(PO4)2(P2O7). The proportion of NaFePO4 impurity phase after fitting calculation is less than 2%, indicating that the precursor can be used to produce a positive electrode material with basically no impurity phase.
[0502] The positive electrode material prepared from the precursor obtained in Example 5 was tested by a carbon-sulfur instrument, and the carbon content of the positive electrode material was measured to be 3.70wt%, and the sulfur content was 0.0364wt%.
[0503] The test methods or standards involved in this application include GB / T 5162-2021 Determination of the tap density of metal powders, GB / T 19587-2017 Determination of the specific surface area of solid substances by gas adsorption BET method, GB / T 19077-2016 Particle size distribution laser diffraction method, YS / T928.3-2013 Chemical analysis methods for nickel, cobalt and manganese hydroxides Part 3: Determination of nickel, cobalt and manganese content by inductively coupled plasma atomic emission spectrometry, etc.
[0504] The performance test method of the positive electrode material in this application is as follows:
[0505] The positive electrode material, conductive carbon black SP, and binder PVDF were mixed into a slurry in a mass ratio of 7:2:1 and then coated on aluminum foil, and then the film was dried in a vacuum drying oven at 110°C for 4 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, and metallic sodium was used as the counter electrode, 1mol / L NaClO4 EC+PC (1:1vol%)+5%FEC was used as the electrolyte, wherein EC was ethylene carbonate, PC was polycarbonate, FEC was a fluoroethylene carbonate additive, and the separator was glass fiber, and assembled into a CR2016 button battery in a glove box.
[0506] The button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=129mAh / g). Figure 8 This is the first week charge and discharge curve of the Na4Fe3(PO4)2(P2O7) electrode in Example 5. In the voltage range of 1.5-4.2V, the reversible specific capacity of the electrode is 110mAh / g, and the average discharge potential is 3.1V, showing a relatively high capacity.
[0507] The compaction density of the positive electrode material in the present application is tested using a UTM7305 microcomputer-controlled electronic pressure testing machine under a pressure of 3 tons, and the test mold is a cylinder with a diameter of 13 mm.
[0508] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A polyanionic precursor, characterized in that: Contains the chemical formula Na q M m+n M' w P x O y · Substances containing H2O; Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; m represents M 2+ The content of M 3+ The content of 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.68≤(m+n+w) / x≤0.80, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, x, and y are selected according to the valence state of M' so that the chemical formula maintains charge balance.
2. The polyanionic precursor according to claim 1, characterized in that One or more of the following conditions are met: (1) M is Fe and Mn; (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y; (3) 0.40≤q / (m+n+w)≤0.65; (4) 0.26≤q / x≤0.60; (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26; (6) 0≤w / (m+n)≤0.05; (7) 0.71≤(m+n+w) / x≤0.77; (8) The valence state of M' is +α, q+2m+3n+αw+5x=2y; (9) The valence state of M' is +α, 1≤α≤5; or, 2≤α≤4; (10) 0≤z / (m+n+w)≤6; or, 0≤z / (m+n+w)≤3; (11) The polyanionic precursor contains phosphate and / or pyrophosphate; (12) The polyanionic precursor contains pyrophosphate, and the P content in the pyrophosphate accounts for more than 10 wt% of the total P content in the polyanionic precursor; (13) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%; (14) In the polyanionic precursor, the content of P is 15wt% to 25wt%; (15) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%; (16) In the polyanionic precursor, the content of S is less than 0.5 wt %; (17) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %; (18) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%; (19) In the polyanionic precursor, the content of the impurity element is less than 3.0 wt %; or, the content of the impurity element is less than 1.5 wt %; (20) In the polyanionic precursor, n(S):n(M+M')≤0.1, or n(S):n(M+M')≤0.06; (21) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, or n(S+N):n(M+M')≤0.06; (22) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, or n(S+N+C):n(P)≤0.06; (23) The polyanionic precursor is in an amorphous state; (24) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ; (25) The BET of the polyanionic precursor is 5 to 25 m 2 / g; (26) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm; (27) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm; (28) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm; (29) The primary particles of the polyanionic precursor are spherical or quasi-spherical; (30) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°; (31) The polyanionic precursor is poorly soluble in water; (32) The polyanionic precursor conforms to the chemical formula Na q M m+n M' w P x O y ·zH2O.
3. A polyanionic precursor, characterized in that Contains the chemical formula Na q M m+n M' w (PO4) e (P2O7) f · Substances containing H2O; Wherein, M is one or more of Fe, Ni, Co, and Mn; M' is one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; m represents M 2+ The content of M 3+ content, 0≤m / (m+n)≤0.35, 0≤w / (m+n)≤0.1, 0.32≤q / (m+n+w)≤0.70, 0.68≤(m+n+w) / (e+2f)≤0.80, 0≤e / (e+2f)≤0.90, 0.1≤2f / (e+2f)≤1, 0≤z / (m+n+w)≤10, and the values of q, m, n, w, e, and f are selected according to the valence state of M' so that the chemical formula maintains charge balance.
4. The polyanionic precursor according to claim 3, characterized in that One or more of the following conditions are met: (1) M is Fe and Mn; (2) The transition metal elements other than M include Ti, V, Cr, Zr, Nb, W, Cr, Cu, Zn, Mo, Sc, and Y; (3) 0.40≤q / (m+n+w)≤0.65; (4) 0.26≤q / (e+2f)≤0.60; (5) 0≤m / (m+n)≤0.33; or, 0≤m / (m+n)≤0.30; or, 0≤m / (m+n)≤0.26; (6) 0≤w / (m+n)≤0.05; (7)0.71≤(m+n+w) / (e+2f)≤0.77; (8) The valence state of M' is +α, q+2m+3n+αw+5(e+2f)=2(4e+7f); (9) The valence state of M' is +α, 1≤α≤5; or, 2≤α≤4; (10) 0≤z / (m+n+w)≤6; or, 0≤z / (m+n+w)≤3; (11) The polyanionic precursor contains phosphate and / or pyrophosphate; (12) The polyanionic precursor contains pyrophosphate, and the P content in the pyrophosphate accounts for more than 10 wt% of the total P content in the polyanionic precursor; (13) In the polyanionic precursor, the content of Na is 4 wt% to 10 wt%; (14) In the polyanionic precursor, the content of P is 15wt% to 25wt%; (15) In the polyanionic precursor, the total content of M and M' is 20wt% to 32wt%; (16) In the polyanionic precursor, the content of S is less than 0.5 wt %; (17) In the polyanionic precursor, the total content of S and N is less than 0.8 wt %; (18) In the polyanionic precursor, the total content of S, N and C is less than 1.0 wt%; (19) In the polyanionic precursor, the content of the impurity element is less than 3.0 wt %; or, the content of the impurity element is less than 1.5 wt %; (20) In the polyanionic precursor, n(S):n(M+M')≤0.1, or n(S):n(M+M')≤0.06; (21) In the polyanionic precursor, n(S+N):n(M+M')≤0.1, or n(S+N):n(M+M')≤0.06; (22) In the polyanionic precursor, n(S+N+C):n(P)≤0.1, or n(S+N+C):n(P)≤0.06; (23) The polyanionic precursor is in an amorphous state; (24) The tap density TD of the polyanionic precursor is 0.9 to 1.4 g / cm 3 ; (25) The BET of the polyanionic precursor is 5 to 25 m 2 / g; (26) The average particle size of the primary particles of the polyanionic precursor is 50 to 200 nm; (27) The average particle size D50 of the secondary particles of the polyanionic precursor satisfies: 1 μm ≤ D50 ≤ 10 μm; (28) The particle size distribution of the polyanionic precursor satisfies: D10≤1 μm, 1 μm≤D50≤10 μm, D90≤50 μm; (29) The primary particles of the polyanionic precursor are spherical or quasi-spherical; (30) In the XRD spectrum of the polyanionic precursor, within the test range of 20°≤2θ≤70°, the peak position of the highest peak is between 26° and 32°; (31) The polyanionic precursor is poorly soluble in water; (32) The polyanionic precursor conforms to the chemical formula Na q M m+n M' w (PO4) e (P2O7) f ·zH2O.
5. A method for preparing a polyanionic precursor, characterized in that: The following steps are involved: Step A: Add M 2+ A metal salt and a first phosphorus source containing pyrophosphate are mixed to obtain a mixed solution, and a first reaction is performed to obtain a mixed solution containing a pyrophosphate salt of a divalent metal M; Step B: adding an oxidant and a second phosphorus source to a mixed solution of pyrophosphate containing a divalent metal M to carry out a second reaction, separating the solid and the liquid after the second reaction, and drying the separated solid to obtain the polyanionic precursor; wherein the first phosphorus source and / or the second phosphorus source contain sodium ions.
6. The method for preparing a polyanionic precursor according to claim 5, characterized in that: One or more of the following conditions are met: (1) The M-containing 2+ The metal salt includes one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt; 2+ The metal salt is one or more of a soluble divalent iron salt, a soluble divalent manganese salt, a soluble divalent nickel salt, and a soluble divalent cobalt salt; (2) The M-containing 2+ The metal salt includes one or more of sulfate, nitrate and chloride; (3) The M-containing 2+ The metal salt also contains a soluble salt of metal M'; (4) the first phosphorus source and / or the second phosphorus source comprises pyrophosphate and / or sodium pyrophosphate; (5) The temperature of the first reaction is 50 to 80° C., and the time of the first reaction is 1 to 10 hours; (6) The oxidant is hydrogen peroxide; (7) the molar amount of phosphorus in the pyrophosphate ion accounts for no less than 70% of the total molar amount of phosphorus in the first phosphorus source and the second phosphorus source; (8) introducing an oxygen-containing gas during the second reaction; (9) The temperature of the second reaction is 55 to 85° C., and the time of the second reaction is 1 to 6 hours; (10) performing aging after the second reaction, wherein the aging time is 5 to 20 hours; (11) The drying temperature is 80 to 120° C.; (12) The molar ratio of phosphorus in the first phosphorus source to that in the second phosphorus source is 2.5 to 3.6:1; (13) The raw materials of the polyanionic precursor do not contain a carbon source.
7. A polyanion sodium ion battery positive electrode material, characterized in that: The raw materials of the sodium ion battery positive electrode material include a polyanion precursor, a sodium source and a carbon source.
8. The polyanion sodium ion battery positive electrode material according to claim 7, characterized in that: The polyanionic precursor is the polyanionic precursor described in claims 1 to 4, or is the polyanionic precursor obtained by the preparation method of the polyanionic precursor described in claims 5 to 6.
9. A polyanion sodium ion battery positive electrode material, characterized in that: The component of the positive electrode material of the polyanion type sodium ion battery is a composite of metal sodium phosphate pyrophosphate and carbon; In the sodium phosphate pyrophosphate metal salt, the metal other than sodium includes M and M' which is not necessarily present; wherein M is one or more of Fe, Ni, Co, and Mn; and M' is selected from one or more of transition metal elements other than M, Mg, Ca, Sr, and Al; The polyanion sodium ion battery positive electrode material meets one or more of the following conditions: (1) The compaction density of the polyanion sodium ion battery positive electrode material is 1.8 to 2.4 g / cm 3 ; (2) The specific surface area of the polyanion sodium ion battery positive electrode material is 5 to 25 m 2 / g; (3) The average particle size of the primary particles of the polyanion sodium ion battery positive electrode material is 100 to 400 nm; (4) The average particle size D50 of the secondary particles of the polyanion sodium ion battery positive electrode material is 1 to 5 μm; (5) The crystal structure of the sodium phosphophosphate metal salt belongs to the Pn21a space group; (6) The chemical formula of the sodium phosphophosphate metal salt is Na4M j M' k (PO4)2P2O7; wherein k / j≤0.1, 2.8≤j+k≤3.2; (7) The S content of the polyanion sodium ion battery positive electrode material is ≤0.08wt%; or, the S content is ≤0.05wt%; (8) The N content of the polyanion sodium ion battery positive electrode material is ≤0.08wt%; or, the N content is ≤0.05wt%.
10. A method for preparing a polyanionic sodium ion battery positive electrode material according to any one of claims 7 to 9, characterized in that: include: The raw materials including the polyanion precursor, the carbon source and the sodium source are mixed, crushed, dried and then sintered to obtain the polyanion sodium ion battery positive electrode material.
11. The preparation method according to claim 10, characterized in that: The preparation method meets one or more of the following conditions: (1) The carbon source is one or more of sucrose, glucose, crystal sugar, cellulose, phenolic resin, polyethylene glycol, polyvinyl pyrrolidone, starch, polyvinyl alcohol, ionic cellulose gum carbon source, and inorganic carbon source; (2) The sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate, and sodium oxalate; (3) The pulverization is grinding or sand milling; (4) The sintering temperature is 500-600° C., and the sintering time is 6-30 hours.
12. A sodium ion battery, characterized in that: The invention comprises the polyanion sodium ion battery positive electrode material according to any one of claims 7 to 9.
13. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 12.
Citation Information
Cited By
Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN121366889A
High-voltage composite sodium ferric phosphate precursor and preparation method thereof
CN121516842A
Preparation method of sodium iron phosphate pyrophosphate with high compact density
CN122877726A